2011
DOI: 10.1186/1471-2431-11-34
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of aerobic fitness and motor skills with memory and attention in preschoolers (Ballabeina): A cross-sectional and longitudinal study

Abstract: BackgroundThe debate about a possible relationship between aerobic fitness and motor skills with cognitive development in children has recently re-emerged, because of the decrease in children's aerobic fitness and the concomitant pressure of schools to enhance cognitive performance. As the literature in young children is scarce, we examined the cross-sectional and longitudinal relationship of aerobic fitness and motor skills with spatial working memory and attention in preschool children.MethodsData from 245 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
131
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(164 citation statements)
references
References 35 publications
15
131
0
8
Order By: Relevance
“…As an example, the reliability of the fitness tests used for the Ballabeina study conducted in Swiss preschool children is reported in several articles [15][16][17][18][19][20], but only one article representing this project is included in the present review [19]. Although inclusion of information on reliability, validity or the relationship with health outcomes of field-based physical fitness tests was a criterion for final inclusion of a study in the review, these terms were not entered in the electronic search and the authors conducted the selection manually.…”
Section: Only One Original Article Per Study Includedmentioning
confidence: 99%
“…As an example, the reliability of the fitness tests used for the Ballabeina study conducted in Swiss preschool children is reported in several articles [15][16][17][18][19][20], but only one article representing this project is included in the present review [19]. Although inclusion of information on reliability, validity or the relationship with health outcomes of field-based physical fitness tests was a criterion for final inclusion of a study in the review, these terms were not entered in the electronic search and the authors conducted the selection manually.…”
Section: Only One Original Article Per Study Includedmentioning
confidence: 99%
“…Assim este processo de intervenção combinada, proposto pelo presente estudo pode proporcionar um equilíbrio das funções cognitivas em suas diversas áreas de desempenho motor de suas variadas funções cinestésicas corporais, no que tange à atividade ludomotora através do ato de brincar melhorando a execução das tarefas cotidianas proporcionalmente, coerente e adequada, traduzindo-se em harmonia e equilíbrio psicomotor que pode otimizar a aprendizagem e a memorização 23 . Portanto pode-se dizer que ao utilizar a frequência entre 8 a 12 HZ, faixa que, segundo Cardoso 12 ; Ribeiro Junior et al 24 , está relacionada com a atenção e a aprendizagem, criou-se um cenário cortical propício a este tipo de evento, o que se pôde comprovar através da superioridade do grupo 2 sobre os demais grupo deste estudo, confirmando-se o valor ou os efeitos positivos que a estimulação cortical combinado com a intervenção ludomotora, pode trazer ao desenvolvimento cinestésico corporal dessas crianças.…”
Section: Discussionunclassified
“…So belegen Bittmann und Kollegen eine enge Korrelation zwischen der stabilen Gleichgewichtsfähigkeit und kognitiven Leistungen (gemessen am Lehrerurteil über die schulischen Lese-Rechtschreib-und RechenLeistungen) von 733 Grundschulkindern aus Brandenburg (Bittmann, Gutschow, Luther, Wessel & Kurths, 2005). Die Arbeitsgruppe um Niederer (Niederer et al, 2011) weist in ihrer Interventionsstudie einen signifikanten Zusammenhang zwischen der Merkfähigkeit von 245 Schweizer Kindergartenkindern und deren nach Intervention verbessertem dynamischem Gleichgewicht nach. Der hinter diesem Effekt vermutete Wirkzusammenhang wird in neuralen Strukturen verortet, wonach sich zerebrale Ressourcen auch in Balanceleistungen widerspiegeln und umgekehrt (Bittmann et al, 2005).…”
Section: Motorikunclassified